Cohesin Is Required for Activation of MYC by Estradiol - McEwan, Miranda V.; Eccles, Michael R.; Horsfield, Julia A. (PLOS ONE, 2012)
Cohesin is best known as a multi-subunit protein complex that holds together replicated sister chromatids from S phase until G2. Cohesin also has an important role in the regulation of gene expression. We previously demonstrated that the cohesin complex positively regulates expression of the oncogene MYC. Cell proliferation driven by MYC contributes to many cancers, including breast cancer. The MYC oncogene is estrogen-responsive and a transcriptional target of estrogen receptor alpha (ERα). Estrogen-induced cohesin binding sites coincide with ERα binding at the MYC locus, raising the possibility that cohesin and ERα combine actions to regulate MYC transcription. The objective of this study was to investigate a putative role for cohesin in estrogen induction of MYC expression. We found that siRNA-targeted depletion of a cohesin subunit, RAD21, decreased MYC expression in ER-positive (MCF7 and T47D) and ER-negative (MDA-MB-231) breast cancer cell lines. In addition, RAD21 depletion blocked estradiol-mediated activation of MYC in ER-positive cell lines, and decreased ERα binding to estrogen response elements (EREs) upstream of MYC, without affecting total ERα levels. Treatment of MCF7 cells with estradiol caused enrichment of RAD21 binding at upstream enhancers and at the P2 promoter of MYC. Enriched binding at all sites, except the P2 promoter, was dependent on ERα. Since RAD21 depletion did not affect transcription driven by an exogenous reporter construct containing a naked ERE, chromatin-based mechanisms are likely to be involved in cohesin-dependent MYC transcription. This study demonstrates that ERα activation of MYC can be modulated by cohesin. Together, these results demonstrate a novel role for cohesin in estrogen-mediated regulation of MYC and the first evidence that cohesin plays a role in ERα binding.